2022
DOI: 10.1002/acr2.11449
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Intention Screening in Patients With Systemic Rheumatic Diseases: Pilot Testing a Standardized Assessment Tool

Abstract: Objective Systemic rheumatic conditions affect reproductive‐aged patients and often require potentially teratogenic medications. We assessed the feasibility and impact of a standardized pregnancy intention screening question (One Key Question [OKQ]) in a large academic rheumatology practice. Methods This 6‐month pilot quality improvement initiative prompted rheumatologists to ask female patients aged 18 to 49 years about their pregnancy intentions using OKQ. We administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Most of the seven studies (35, 45, 46, 48, 52, 54) reporting documentation of reproductive counselling measured a significant increase after implementation of the RLP with intervention arm rates ranging from 58.4% in a study of the OKQ (54) to a maximum of 93.1% in a study of the MyPath tool (51). Knowledge and awareness also appeared to increase across the seven studies measuring this outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the seven studies (35, 45, 46, 48, 52, 54) reporting documentation of reproductive counselling measured a significant increase after implementation of the RLP with intervention arm rates ranging from 58.4% in a study of the OKQ (54) to a maximum of 93.1% in a study of the MyPath tool (51). Knowledge and awareness also appeared to increase across the seven studies measuring this outcome.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 One 6-month quality improvement study demonstrated the feasibility of implementing One Key Question in an academic rheumatology setting; although uptake was low, the use of any pregnancy intention screening tool was associated with increased contraceptive documentation and OB/GYN referrals. 18 Furthermore, the European League Against Rheumatism (EULAR) recommendations highlight the importance of counselling women with SLE and/or APS about fertility issues and pregnancy prevention in high-risk scenarios. 19 Guidelines and prior studies highlight the need for rheumatologists to collaborate with OB/GYNs in the delivery of reproductive healthcare for patients with RD.…”
Section: Family Planningmentioning
confidence: 99%
“…[22][23][24] While rheumatologists do feel responsible for contraceptive counselling, 20 they may be uncomfortable with this area and may not provide adequate counselling. 12,18,20,23,25 Young women with RD often turn to OB/GYNs for information and support. 13 A 2021 US electronic health record-based study found documentation of contraceptive counselling to be poorly standardized and inadequate.…”
Section: Contraception and Pregnancy Terminationmentioning
confidence: 99%
“…OKQ has shown mixed effects on patient satisfaction, low uptake in an EMR-based primary care intervention and was associated with a decrease in documented pregnancy intention screening in a recent pilot study of veterans’ healthcare [ 6 – 9 ]. A recent pilot study by our group found that in an intervention among rheumatologists, 9% of eligible patients were screened with OKQ and screening responses were correlated with contraceptive documentation and referrals; however, that pilot did not include the full OKQ training for providers [ 10 ]. A large cohort study included a contraceptive preferences survey as a research procedure and not a standard component of the clinical encounter and found that the PATH questions predicted contraceptive method choice, with those expressing a desire to wait to become pregnant and less happiness at the idea of pregnancy now being more likely to choose the most effective contraceptive methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%